Molecular techniques applied to investigations of abundance of the ammonia oxidizing bacteria and ammonia oxidizing archaea microorganisms in the environment - Amjed Ginawi; Yan Yunjun (Institute of Advanced Engineering and Science, 2019)
This review shows regards of the recently experienced concerning the environments of ammonia oxidizing bacteria (AOB), ammonia oxidizing archaea (AOA) microorganisms, and denitrifying microbes. The advancements of molecular biology techniques have encouraged staggeringly to the fast recent developments in the sector. Various methods for implementing so are discussed. The function of AOB, AOA, and denitrifying microorganism composition was investigated through a high throughput of the 16S rRNA amplicon sequencing protocol. There is potential to observe the specific species appearance of these microorganisms in each environment and get to the evaluated relative abundance of several kinds. There is information indicated which the structure of denitrifying and nitrifying group was monitored field to significant fluctuations and the complexes, together in space and in time. More effort is required to enhance and isolate those microorganisms that common of the progressions and to function them through the compound of molecular techniques, biochemical and physiological. However, the investigation with deoxyribonucleic acid (DNA), antibodies, and the polymerase chain reaction (PCR) was preferred mainly to report the composition of chemolithoautotrophic bacteria, surveys of their characteristics in environmental that needed quantification at the transcriptional level is presently not available.